2020
DOI: 10.1021/acsbiomaterials.0c01132
|View full text |Cite
|
Sign up to set email alerts
|

Nano- and Microformulations to Advance Therapies for Visceral Leishmaniasis

Abstract: Visceral leishmaniasis (VL) is a deadly, vectorborne, neglected tropical disease endemic to arid parts of the world and is caused by a protozoan parasite of the genus Leishmania. Chemotherapy is the primary treatment for this systemic disease, and multiple potent therapies exist against this intracellular parasite. However, several factors, such as systemic toxicity, high costs, arduous treatment regimen, and rising drug resistance, are barriers for effective therapy against VL. Material-based platforms have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Generation of new AmB derivatives 43 , 44 or its nano-formulation with reduced toxicity 24 , 45 47 was reported with some success. But due to the lack of vaccine 48 and drug resistance and toxicity associated with AmB, the idea of nano and micro-formulation 49 , natural product-based drug-delivery 6 using flavonoids or its formulation 50 , 51 , marine products 52 and even drug-repurposing 53 have gained significant attention for the treatment of various forms of leishmaniasis. In this study, we have confirmed the antileishmanial efficacy of CA, a natural FA that is already known to have antibacterial/antifungal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of new AmB derivatives 43 , 44 or its nano-formulation with reduced toxicity 24 , 45 47 was reported with some success. But due to the lack of vaccine 48 and drug resistance and toxicity associated with AmB, the idea of nano and micro-formulation 49 , natural product-based drug-delivery 6 using flavonoids or its formulation 50 , 51 , marine products 52 and even drug-repurposing 53 have gained significant attention for the treatment of various forms of leishmaniasis. In this study, we have confirmed the antileishmanial efficacy of CA, a natural FA that is already known to have antibacterial/antifungal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The neglected tropical disease leishmaniasis (caused by around 20 species of the genus Leishmania) is the second most common parasitic disease after malaria and affects close to 1 million people yearly. 176 It is endemic in places like Bihar, the second poorest state in India. 177,178 Although there are several FDA approved and preclinical treatments for leishmaniasis, 176 amphotericin B is the first-line treatment in endemic areas.…”
Section: Success Can Come In Small Packagesmentioning
confidence: 99%
“…31 The applications of nanoparticles (NPs), due to their biodegradability, biocompatibility, stability, surface-modifiable abilities, and facilitating pharmacokinetics, 33 have gained much attention in the development of effective conjugated nanotherapeutics in the management of parasitic infections through intracellular delivery, particularly against Leishmania infections. 34 It has been reported that in achieving effective leishmaniasis therapy, macrophage-targeted drug delivery plays a crucial role, and this strategy could be accomplished through mannose receptor-mediated endocytosis of the nanoparticulate systems. 35 Among the various kinds of nanomaterials, nanoemulsions have shown safety, biodegradability, stability, and drug targetability, and thus have evolved as a novel strategy for targeting ALA in leishmaniasis therapy.…”
Section: Introductionmentioning
confidence: 99%